Requisitos para contrata????o de servi??os em computa????o em nuvem pela Administra????o P??blica Federal - Lopes, Thiago Ferreira (2015)
The constantly rising business opportunities has forced IT to move toward an adaptive utility model by adopting the cloud computing model, in most cases, due to the speed and low cost offered by this model. However, there are still some issues that are not clear in the adoption of this model, both for customers and for service providers that still experience difficulties in specific segments calls that require the processing of large loads, specific issues related to security, laws and regulations. This research presents the specific requirements that must be considered in preparing the service contract with the cloud computing provider to the Federal Public Administration. With these requirements, evaluations were made of notices published in recent years in order to verify that the requirements were found used or not.